Professional soccer player neuromuscular responses and perceptions to acute whole body vibration differ from amateur counterparts - Cloak, R.; Lane, A.; Wyon, M. (Journal of Sports Science & Medicine, 2016)
Acute whole body vibration (WBV) is an increasingly popular training technique amongst athletes immediately prior to performance and during scheduled breaks in play. Despite its growing popularity, evidence to demonstrate its effectiveness on acute neuromuscular responses is unclear, and suggestions that athlete ability impacts effectiveness warrant further investigation. The purpose of this study was to compare the neuromuscular effects of acute WBV and perceptions of whether WBV is an effective intervention between amateur and professional soccer players. Participants were 44 male soccer players (22 professional and 22 amateur; age: 23.1 ± 3.7 years, body mass: 75.6 ± 8.8 kg and height: 1.77 ± 0.05 m). Participants in each group were randomly assigned to either an intervention of 3 x 60 s of WBV at 40 Hz (8mm peak-to-peak displacement) or control group. Peak knee isometric force, muscle activation and post activation potentiation (PAP) of the knee extensors along with self-report questionnaire of the perceived benefits of using the intervention were collected. A three-way ANOVA with repeated measures revealed professional players demonstrated a significant 10.6% increase (p < 0.01, Partial Eta2 = 0.22) in peak knee isometric force following acute WBV with no significant differences among amateur players. A significant difference (p < 0.01, Partial Eta2 = 0.16) in PAP amongst professional players following acute WBVT was also reported. No significant differences amongst amateur players were reported across measurements. Results also indicated professional players reported significantly stronger positive beliefs in the effectiveness of the WBV intervention (p < 0.01, Partial Eta2 = 0.27) compared to amateur players. Acute WBV elicited a positive neuromuscular response amongst professional players identified by PAP and improvements in knee isometric peak force as well as perceived benefits of the intervention, benefits not found among amateur players.